2017
DOI: 10.1590/s1677-5538.ibju.2016.0629
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of miniaturized percutaneous nephrolitotomy in infants: single centre experience

Abstract: Objectives:The present study was aim to evaluate the safety and efficacy of Mini-PNL to treat kidney stones in patients aged <3 years. This is the one of the largest series in the literature in this age group of patients.Material and methods:From May 2012 to April 2016, the medical records of 74 infant patients who underwent mini-PNL for renal stones were reviewed retrospectively. All infants were evaluated with the plain abdominal radiograph, urinary ultrasound, non-contrast computerized tomography and/or int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 35 publications
1
7
1
Order By: Relevance
“…In another series of 135 children with an average age of 8.9 years, Salah et al reported a 98.5% SFR [10]. Pelit et al reported a SFR of 84.7% and 94.4% after single and additional sessions respectively [11]. In the present study, patients' records revealed that on the first postoperative day, complete stone-free state was achieved in 87.1% of cases (74/85).…”
Section: Discussionsupporting
confidence: 55%
“…In another series of 135 children with an average age of 8.9 years, Salah et al reported a 98.5% SFR [10]. Pelit et al reported a SFR of 84.7% and 94.4% after single and additional sessions respectively [11]. In the present study, patients' records revealed that on the first postoperative day, complete stone-free state was achieved in 87.1% of cases (74/85).…”
Section: Discussionsupporting
confidence: 55%
“…Percutaneous nephrolithotomy (PCNL) is recommended for the treatment of larger stones, since it has a good success rate; however, the complication rates have been reported to be up to 25%[5]. With advancements in techniques and technologies, miniaturized PCNL (mini-PCNL), defined as a PCNL involving the use of smaller nephroscopes[6], can be performed effectively to manage kidney stones with high stone free rates and low complications[7]. The two surgical procedures have different advantages associated with the treatment of stones of different sizes affecting the urinary system[8-10].…”
Section: Introductionmentioning
confidence: 99%
“…The isolated products were fully characterized by FT-IR, 1 HNMR, and 13 CNMR spectroscopy. All the compounds had physical and spectroscopic data identical to those known xanthenes (Table 3) [41][42][43][44].…”
Section: Resultsmentioning
confidence: 99%